Populist and Pro-Violence State Religion The Diyanet's Construction of Erdoğanist Islam in Turkey - Yilmaz, Ihsan; Albayrak, Ismail (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This book explores state-religion relations under a populist authoritarian ruling party in Turkey. In doing so, it investigates how the ruling Justice and Development Party (AKP) instrumentalizes state-controlled religion to further, defend, legitimatize and propagate its authoritarian populist political agenda in a constitutionally secular nation-state. To exemplify this, the authors examine the Friday sermons delivered weekly in every mosque in Turkey by the Turkish State's Directorate of Religious Affairs (Diyanet). By analyzing all sermons delivered between 2010-2021, the book shows how the Diyanet has enthusiastically adopted AKP's increasingly Islamist, authoritarian, civilisationist, militarist and pro-violence populism since 2010, and how it has tried to socially engineer beliefs in line with this ideology. Ihsan Yilmaz is the Research Professor and Chair of Islamic Studies and Intercultural Dialogue at the Alfred Deakin Institute for Citizenship and Globalisation, Deakin University, Melbourne, Australia. He has conducted mixed-method research on nation-building, citizenship, Islam-state-law relations in majority and minority contexts (Turkey, Pakistan, Egypt, Indonesia, UK, USA and Australia), authoritarianism, Islamism, populism, transnationalism, ethno-religious and political minorities, securitisation, political participation and intergroup relations. He was Professor of Political Science at Istanbul Fatih University (2008-2016), Lecturer in Law, Social Sciences and Politics at SOAS, University of London (2001-2008), and a fellow at Centre for Islamic Studies, the University of Oxford (1999-2001). Ismail Albayrak is the Professorial Fellow at the Australian Catholic University, Melbourne. He has worked on Islamic studies and specifically on Qur'anic Studies, Classical Exegesis, Contemporary Approaches to the Qur'an and Orientalism. He is also interested in the place of Muslim communities and their activities in globalizing world together with a focus on interfaith dialogue. In line with these areas of interest, he has built a strong teaching and research track record in the study of Islam and complementary understanding of interfaith principles. His recent publications have focused on Islamic studies, Qur'anic studies, Interfaith dialogue, Muslims in modern world, Islamic movements and Islamic mysticism.
Chapter 1 The Mosque and the State in Turkey -- Chapter 2 The Kindred Evolution of the Turkish State and Diyanet -- Chapter 3 Redefining Diyanet in the AKP Era -- Chapter 4 Swinging between Turkish Nationalism and Global Pan-Islamism -- Chapter 5 Militarism, Necrophily, Glorification of Martyrdom and Jihadism -- Chapter 6 Securitisation, Demonization and De-humanisation of AKP's Opponents -- Chapter 7 Conspiracy Theories and Politics of Victimhood -- Chapter 8 Populist Civilizationism, Otherization of Christians, and Antagonism Towards Interfaith Dialogue -- Chapter 9 The Future of the Mosque-State Relations in Turkey.
Keywords: Religion and politics; Communication in politics; Politics and Religion; Political Communication